SOCIAL INTERACTION AND NEUROSES (THE FAMILY AND THE PRIMARY GROUP): A PILOT STUDY1 - Sethi, B. B. (Medknow Publications, 1981)
The present work examines the social interaction with the primary group of 30 neurotic patients and 30 matched controls. A comparison of the degree of family jointness in the two groups was also done keeping in view the nature of Indian family system and to find out the association, if any, it bears to social interaction. Evaluation instruments were Social Interaction Schedule (Henderson et al., 1978) and Khatri's Scale to Measure Jointness of Families in India (1970). The findings indicate that neurotic patients do not have a deficient primary group, as far as the numerical size and the duration and type of interaction is concerned. However, the patients appear to be less active than controls in making contacts with members of their primary group outside their household. Further, our group of patients perceived their personal lives to be deficient in some respects. Patients and controls did not differ with regard to the degree of family jointness as measured on Khatri's Scale.